1993
DOI: 10.1007/bf02260912
|View full text |Cite
|
Sign up to set email alerts
|

The effects of L-threo-3,4-dihydroxyphenylserine on the total norepinephrine and dopamine concentrations in the cerebrospinal fluid and freezing gait in parkinsonian patients

Abstract: We studied the effects of L-threo-DOPS (L-DOPS) on the concentrations of total (conjugated and unconjugated) dopamine (DA) and norepinephrine (NE) in the cerebrospinal fluid (CSF) of parkinsonian patients with freezing phenomenon. The NE concentration increased remarkably and dose-dependently after administration of L-DOPS in both L-dopa/carbidopa-pretreated and untreated patients. The DA concentration also increased mildly but significantly in L-dopa/carbidopa-untreated patients. Freezing phenomenon improved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
1
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 18 publications
3
42
1
1
Order By: Relevance
“…Beneficial effects on freezing, gait impairment, retropulsion, and postural instability were noted in small, poorly controlled studies. 93,94 Pending further evidence, there is presently no place for L-threo-DOPS or other nondopaminergic compounds in daily clinical practice. …”
Section: Treatment Drug Treatmentmentioning
confidence: 99%
“…Beneficial effects on freezing, gait impairment, retropulsion, and postural instability were noted in small, poorly controlled studies. 93,94 Pending further evidence, there is presently no place for L-threo-DOPS or other nondopaminergic compounds in daily clinical practice. …”
Section: Treatment Drug Treatmentmentioning
confidence: 99%
“…Other agents that are being considered as nondopaminergic PD therapeutics include modulators of the noradrenergic system. In small open-label studies, the epinephrine precursor L-threo-DOPS was found to have beneficial effects on freezing and gait disturbances in PD patients (Tohgi et al, 1993;Giladi, 2008;Devos et al, 2010). Furthermore, methylphenidate, a mixed dopamine and noradrenaline reuptake inhibitor, was found to show benefit on gait and freezing scores in a randomized controlled trial of 17 advanced PD patients , but results of a more recent trial in 27 PD patients revealed that methylphenidate did not improve gait and tended to worsen measures of motor functions, sleepiness, and quality of life (Espay et al, 2011).…”
Section: Non-dopaminergic Therapiesmentioning
confidence: 99%
“…From preclinical and clinical studies involving measurements of plasma and CSF levels of NE and metabolites after systemic L-DOPS administration, it appears that relatively little of circulating L-DOPS enters the central nervous system unchanged (40,103). In rats, L-DOPS has only about 1/4 the ability of L-DOPA to traverse the blood-brain barrier (48), and the amount of increase of central NE by L-DOPS is actually less than that from L-DOPA.…”
Section: Clinical Pharmacokinetics and Metabolic Fate Of L-dopsmentioning
confidence: 99%
“…In rats, L-DOPS has only about 1/4 the ability of L-DOPA to traverse the blood-brain barrier (48), and the amount of increase of central NE by L-DOPS is actually less than that from L-DOPA. In humans, CSF levels of NE do increase, especially in patients treated concurrently with carbidopa (103,104).…”
Section: Clinical Pharmacokinetics and Metabolic Fate Of L-dopsmentioning
confidence: 99%
See 1 more Smart Citation